Impact of standard and long-lasting ivermectin formulations in cattle and buffalo on wild Anopheles survival on Sumba Island, Indonesia - Kevin C. Kobylinski; Tri B. T. Satoto; Wisnu Nurcahyo; Yudi Ratna Nugraheni; Vincentius A. Testamenti; I Putu B. A. Winata; Yosua L. Pono; Diana Timoria; Piyanan Assawasuwannakit; Mary Chambers; J. Kevin Baird; Joel Tarning; et al. (Scientific Reports)
Abstract The mosquito-lethal effect of commercially available standard and long-lasting ivermectin formulations were evaluated in cattle and buffalo against wild-caught Anopheles on Sumba Island, Indonesia. Cattle have substantially higher blood-level concentrations of ivermectin compared to buffalo after receiving similar doses, irrespective of formulation. In total, nine Anopheles species were captured to assess the mosquito-lethal effects of ivermectin with susceptibility ranked from lowest to highest: An. flavirostris < An. aconitus < An. annularis < An. tessellatus < An. maculatus < An. sundaicus < An. vagus < An. kochi < An. barbirostris. The duration of mosquito-lethal effect of long-lasting ivermectin was superior to standard ivermectin and in cattle it well exceeded the WHO criteria for new endectocides having a mortality hazard ratio greater than 4 through 30 days after administration. Buffalo may require higher doses of long-lasting ivermectin to achieve similar mosquito-lethal effects observed in cattle. Of the four hosts evaluated buffalo were the most attractive to Anopheles followed by cattle then horse and finally humans. This study demonstrates, for the first time, the superiority of a commercially available long-lasting ivermectin formulation for the potential deployment of mass ivermectin treatment of livestock as a vector control tool for malaria elimination in Southeast Asia.